The school participation effect: investigating violence and formal education among girls in the Democratic Republic of the Congo. Issue 5 (3rd September 2019) - Landis, Debbie; Yu, Gary; Tanner, Sophie; Karungu, Caroline; Mallinga, PA; Falb, Kathryn; Stark, Lindsay
Abstract: Little is known about the differential experiences with violence among girls in conflict-affected societies based on their involvement in formal education. A quantitative survey was conducted with girls between the ages of 10–14 across 14 sites in South Kivu, Democratic Republic of the Congo. The prevalence of three forms of violence was estimated across four levels of participation in formal education, and multivariable mixed effects logistic regression models were used to compare girls' increasing levels of education to those who reported never attending school. Trend tests across the four levels of education were conducted for violence outcomes. Girls' higher levels of participation in formal education were significantly associated with lower reported rates of physical and sexual violence. Findings suggest a significant protective effect of formal education on girls from physical and sexual violence. Findings also suggest a significant relationship between girls' age and risk of experiencing physical and sexual violence.